Comparative Study Of Community Tourism Development Models In Baluran, Situbondo, And Banyuwangi National Parks - Hasana, Mou’idhotul; Razak, Abdur (Journal of Business Social and Technology, 2025)
Baluran National Park, which spans across Situbondo and Banyuwangi Regencies, presents an important case for understanding how different regional strategies affect community-based tourism (CBT) outcomes. These two regions employ distinct governance models in managing their tourism potential, resulting in varied levels of community participation, technological integration, and institutional readiness. This study aims to examine and compare community-based tourism development models applied in two strategic areas, namely Baluran National Park, located in Situbondo Regency, and Banyuwangi Regency. This study will focus on Community Capacity Building Efforts, local citizen participation. This study employs a qualitative approach, drawing on literature studies from various scientific journal references and academic literature. The findings of this study indicate that the approach to tourism development in each regional regulation, particularly in Situbondo, emphasizes local output as the foundation for its development. This study suggests that policy harmony and increasing the capacity of local communities are essential foundations for sustainable tourism development.